2022
DOI: 10.15252/embr.202153468
|View full text |Cite
|
Sign up to set email alerts
|

TRIM33 drives prostate tumor growth by stabilizing androgen receptor from Skp2‐mediated degradation

Abstract: Androgen receptor (AR) is a master transcription factor that drives prostate cancer (PCa) development and progression. Alterations in the expression or activity of AR coregulators significantly impact the outcome of the disease. Using a proteomics approach, we identified the tripartite motif‐containing 33 (TRIM33) as a novel transcriptional coactivator of AR. We demonstrate that TRIM33 facilitates AR chromatin binding to directly regulate a transcription program that promotes PCa progression. TRIM33 further st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…Hierarchical clustering of the 10% most differentially expressed genes showed that replicate samples clustered together based on (i) E2 treatment and (ii) the shRNA construct. Hallmark pathway analysis of RNA-seq profiles showed that the set of genes downregulated by shTRIM33 during E2 treatment was enriched for pathways related to DNA repair, the G2M checkpoint, and E2F Targets ( Figure 2 D), pathways in line with known effects of TRIM33 [ 33 , 34 , 35 , 36 , 37 ]. The set of genes upregulated by shTRIM33 during E2 treatment was enriched for estrogen response pathways ( Figure 2 D); these observations parallel the RT-qPCR results showing elevated levels of select ER-inducible transcripts ( PDZK1 , PR ) with TRIM33 knockdown upon supplementation with E2 ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Hierarchical clustering of the 10% most differentially expressed genes showed that replicate samples clustered together based on (i) E2 treatment and (ii) the shRNA construct. Hallmark pathway analysis of RNA-seq profiles showed that the set of genes downregulated by shTRIM33 during E2 treatment was enriched for pathways related to DNA repair, the G2M checkpoint, and E2F Targets ( Figure 2 D), pathways in line with known effects of TRIM33 [ 33 , 34 , 35 , 36 , 37 ]. The set of genes upregulated by shTRIM33 during E2 treatment was enriched for estrogen response pathways ( Figure 2 D); these observations parallel the RT-qPCR results showing elevated levels of select ER-inducible transcripts ( PDZK1 , PR ) with TRIM33 knockdown upon supplementation with E2 ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 96%
“…While the effects of NCOA3 (AIB1, SRC3) and NCOR2 (SMRT) on ER are well known [ 31 , 32 ], the effects of TRIM33 on ER have not yet been reported. In conjunction with TRIM33 being identified by all three interactomes, further support for investigating the role for TRIM33 in ER+ breast cancer comes from findings in prostate cancer cells where TRIM33 modulates the activity of another nuclear hormone receptor, the androgen receptor [ 33 ]. In validation experiments, proximity labeling was performed with MCF-7/Turbo-ER cells treated with +/− E2 for 24 h. Biotinylation of TRIM33 was appreciably higher in E2-treated cells ( Figure 1 E), suggesting an estrogen-induced interaction of Turbo-ER with TRIM33.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cullin 3 (CUL3)-based E3 ligase SPOP polyubiquitinates AR in a manner that is regulated by S648 and T649 in the hinge region ( An et al, 2014 ). In addition to targeting AR for proteasomal degradation ( Khan et al, 2006 ; Rees et al, 2006 ; Chen et al, 2022 ), SPOP also polyubiquitinates and mediates the degradation of AR co-regulator SRC-3 ( Li et al, 2011 ; Geng et al, 2014 ), thus impacting AR transcriptional activity in two ways. Siah2 adds K48-linked polyubiquitin chains to regulate the level of transcriptionally inactive AR (NCORC1-bound AR) ( Qi et al, 2013 ; Jing et al, 2018 ).…”
Section: Androgen Receptor Lifecycle and Ubiquitination Of Androgen R...mentioning
confidence: 99%
“…Siah2 adds K48-linked polyubiquitin chains to regulate the level of transcriptionally inactive AR (NCORC1-bound AR) ( Qi et al, 2013 ; Jing et al, 2018 ). Skp2 polyubiquitinates AR at K848 ( Li et al, 2014 ) and targets it for proteasomal degradation ( Li et al, 2014 ; Chen et al, 2022 ). AHR acts on AR as part of a CUL4 complex ( Ohtake et al, 2007 , 2009 ).…”
Section: Androgen Receptor Lifecycle and Ubiquitination Of Androgen R...mentioning
confidence: 99%